Answer:
joe=6
Sam=11
Explanation:
lets see...
i explain 1by1
firstly we know that joe is 5 - 3 x Sam
(read the sentences VERY CAREFULLY)
then, we put Sam as math variable "s"
it will be; 5-3 x S
![5 - 3 * s](https://img.qammunity.org/2021/formulas/mathematics/high-school/mi9hvaop76xnzvrvuuoc7ujm3dqgoncliq.png)
the total of their age is 28
![5 - 3 * s = 28](https://img.qammunity.org/2021/formulas/mathematics/high-school/hq4u1nye4247ap64563epcvpao12583j4i.png)
simplify it
it will be 5-S3=28
then you will get 11 right
that will be sam's age
-5 and it will be Joe's age